Advances in Carbon Based Nanomaterials for Bio-Medical Applications - Gupta, Tejendra K.; Budarapu, Pattabhi Ramaiah; Chappidi, Sivakumar Reddy; Y.B., Sudhir Sastry; Paggi, Marco; Bordas, Stephane P. (Current Medicinal Chemistry, 2019)
The unique mechanical, electrical, thermal, chemical and optical properties of carbon based nanomaterials (CBNs) like: Fullerenes, Graphene, Carbon nanotubes, and their derivatives made them widely used materials for various applications including biomedicine. Few recent applications of the CBNs in biomedicine include: cancer therapy, targeted drug delivery, bio-sensing, cell and tissue imaging and regenerative medicine. However, functionalization renders the toxicity of CBNs and makes them soluble in several solvents including water, which is required for biomedical applications. Hence, this review represents the complete study of development in nanomaterials of carbon for biomedical uses. Especially, CBNs as the vehicles for delivering the drug in carbon nanomaterials is described in particular. The computational modeling approaches of various CBNs are also addressed. Furthermore, prospectus, issues and possible challenges of this rapidly developing field are highlighted.
Keywords: functionalization